2021
DOI: 10.1080/07853890.2021.1905872
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages expressing TREM-1 are involved in the progression of HPV16-related oropharyngeal squamous cell carcinoma

Abstract: Introduction Many types of research have been performed to improve the diagnosis, therapy, and prognosis of oropharyngeal carcinomas (OP-SCCs). Since they arise in lymphoid-rich areas and intense lymphocytic infiltration has been related to a better prognosis, a TREM-1 putative function in tumour progression and survival has been hypothesized. Materials and methods Twenty-seven human papillomavirus (HPV) 16 + OP-SCC specimens have been analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Interestingly, given the lack of response between the CAFs and HPV-positive cells which we have again demonstrated, many more M1/M2 macrophages (which often express OPN) have been identified in HPV+ stroma, which, if at a high level, has been associated with poor regional control ( 49 ). It has also been demonstrated that macrophages expressing TREM1 are important in the progression of HPV+ OPSCC ( 50 ) and that fibroblasts with a matrix-CAF phenotype collaborate with SPP1-expressing TAMs to promote tumour progression in HNSCC ( 51 ). This may indicate a greater importance in the role of TAMs in the HPV-positive TME, which will require further investigation, as an additional element to the OPSCC-fibroblast model.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, given the lack of response between the CAFs and HPV-positive cells which we have again demonstrated, many more M1/M2 macrophages (which often express OPN) have been identified in HPV+ stroma, which, if at a high level, has been associated with poor regional control ( 49 ). It has also been demonstrated that macrophages expressing TREM1 are important in the progression of HPV+ OPSCC ( 50 ) and that fibroblasts with a matrix-CAF phenotype collaborate with SPP1-expressing TAMs to promote tumour progression in HNSCC ( 51 ). This may indicate a greater importance in the role of TAMs in the HPV-positive TME, which will require further investigation, as an additional element to the OPSCC-fibroblast model.…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, FoxP3+ Treg cells are more likely to be associated with a poor clinical outcome. 10,36,51 Otherwise, conflicting data are due to insufficient analysis of small populations such as NK cells, 70 the significance of tumor-associated macrophages (TAM), 37,44,47,71,72 mast cell infiltration, 27 and monocyte infiltration. 67 All of these markers were investigated in sample sizes ranging from 27 to 168 patients.…”
Section: Cd3+foxp3+mentioning
confidence: 99%
“…In the case of HPV +OSCC, an anti-HPV T-cell immune response could increase the overall antitumor T-cell response and could contribute to a better clinical outcome. The anti-HPV T-cell specific response has been reported to be associated with the presence of T RM and with a better 71 Ou 2019, 72 Snietura 2020, 37…”
Section: Cd3+foxp3+mentioning
confidence: 99%
“…The expression of DNA repair protein, especially the homologous recombination protein RAD51, is upregulated in HPV‐positive HNSCC (Holcomb et al., 2020). TREM‐1 expressed on myeloid cells correlates to HPV‐positive OPSCC progression (Azzimonti et al., 2021). The stimulator of interferon genes is dampened by NLRX1, leading to immune escape in HPV16‐positive HNSCC (Lu et al., 2018; Luo et al., 2020; Shaikh et al., 2019).…”
Section: Human Papillomavirusmentioning
confidence: 99%
“…The expression of DNA repair protein, especially the homologous recombination protein RAD51, is upregulated in HPV-positive HNSCC (Holcomb et al, 2020). TREM-1 expressed on myeloid cells correlates to HPV-positive OPSCC progression (Azzimonti et al, 2021).…”
Section: Human Papillomavirusmentioning
confidence: 99%